PERTANGGUNGJAWABAN NOTARIS TERHADAP AKAD PEMBIAYAAN FIKTIF (STUDI PUTUSAN PN BOGOR NO.:125/PID.SUS/2014/PN.BGR.) - RAHMA SARI (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. T. Keizerina Devi A2. Edy Ikhsan3. Suprayitno In channeling financing and doing any business activities, Bank Syariah and UUS have to do any methods which do not harm Bank Syariah and the interest of clients who entrust their deposit. However, in the case of the Bogor District Court’s Verdict No. 125/PID.SUS/2014/PN.Bgr, there were 113 fictive financing at PT. BSM which involved the defendant, a Notary who was imposed criminal sanction of 5 months and 6 days because it was evident that he had been judicially correct in violating Article 264, paragraph 1 of the Penal Code in committing authentic deed forgery. The objective of the research was to find out the legal aspect of sharia financing according to Akad Murabahah, a Notary’s legal liability for facilitating sharia financing according to Akad Murabahah and for fictive financing deeds in the Bogor District Court’s Verdict No. 125/PID.SUS/2014/PN.Bgr.Keywords: Akad Murabahah, Notary, Legal Liability